2014
DOI: 10.1186/2193-1801-3-216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum β-lactamase positive bacteria in radiologically positive urinary tract infection

Abstract: The increase in antibiotic resistance among uropathogens is a global problem. The present study was an effort to assess the current antibiotic resistance pattern and plasmid profiles of some multi drug resistant bacteria isolated from urinary tract infection (UTI). Among 44 clinical samples of radiologically positive UTI, 44 microorganisms belonging to 9 genus were isolated. Of the patients, 24 were female and 20 were male. Highest incidence was found in age group of 30–45 years. Total bacterial count of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
7
13
1
Order By: Relevance
“…The highest significant growth (33%) was observed in the age groups of 21-40 years followed by 40 years or above (24.62%) and 0-20 years (23.53%) age groups. According to a study in 2014 [23] UTIs was more prevalent in age group of 30-45 years which correlates our findings. Another, UTIs related study in Bangladesh reported that most of the UTIs cases occurred in 21-30 years old (44%) age groups, followed by 41-50 years old (37%) age groups [24].…”
Section: Resultssupporting
confidence: 78%
“…The highest significant growth (33%) was observed in the age groups of 21-40 years followed by 40 years or above (24.62%) and 0-20 years (23.53%) age groups. According to a study in 2014 [23] UTIs was more prevalent in age group of 30-45 years which correlates our findings. Another, UTIs related study in Bangladesh reported that most of the UTIs cases occurred in 21-30 years old (44%) age groups, followed by 41-50 years old (37%) age groups [24].…”
Section: Resultssupporting
confidence: 78%
“…coli isolates were resistant to at least one cephalosporin. Similar rates of antimicrobial resistance were documented in other studies from Bangladesh 19 , Iran 29 and India 30 . However, compared to reports from Nepal, we observed a considerable increase in resistance against penicillins, aminoglycosides, quinolones and ceftriaxone.…”
Section: Discussionsupporting
confidence: 72%
“…10,[16][17][18][19] Antibiotic sensitivity patterns were also similar. [6][7][8][9][10][16][17][18] Current study had some limitations. It was a single center study, comprising small number of study population over a short period of time and most of our study participants were diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In Bangladesh, only a few studies were reported on ESBL-positive organisms, mostly describing their prevalence and antibiotic sensitivity patterns. [5][6][7][8][9] Diabetes mellitus (DM), past history of UTI and prior antibiotic use are reported risk factors for UTI due to ESBL-positive organisms. 10,11 In this study, we have tried to evaluate the frequency of UTI due to ESBL-positive Escherichia coli and Klebsiella pneumoniae, their antibiotic sensitivity patterns and risk factors.…”
Section: Introductionmentioning
confidence: 99%